POLITIK HUKUM DALAM PEMBANGUNAN HUKUM NASIONAL PASCA AMANDEMEN UNDANG-UNDANG DASAR 1945 - Bambang Sugianto (VIVA THEMIS, 2018)
ABSTRACTPolitics of law in the development of national law after the amendment of the 1945 Constitution can be summarized as follows: a) The Birth of the Form of the State of Indonesia is a Unitary State, b) The Form of Indonesian Government is a Republic with a presidential system, c) The State of Indonesia is a State of Law, and ) The structure of the State of Indonesia consists of central government and local government.The central government institutions consist of legislative, executive and judicial institutions in accordance with the theory of separation of power from Trias Politics and also the principle of check and balances among state institutions. While the structure of regional institutions consists only of the legislative and executive institutions with the administration of government based on the concept of autonomy in the form of political decentralization (devolution).In addition, the Amendment of the 1945 Constitution upheld the system of Judicial Power which is in the hands of the Supreme Court in the process of law enforcement. Now the power of imperialism consists of the Supreme Court, Judicial Commission and the Constitutional Court. Including the change of some institutions of the MPR is no longer the institution in order to implement the sovereignty of the people. The executive is no longer the institution that dominates in the formation of the law so that the Checks and Balance process in the political system and constitutional system, is very important because the three restaurants especially the Legislature where all this time in the making of the law is dominated by the executive both the initiative and the endorsement of its legislation.The very basic in the politics of law and post-amendment law development is the democratic system in which the head of state and the head of the region are elected through representation and now the sovereignty is in the hands of the people, as well as the concept of The Rule Of Law State law which guarantees and protects the rights of the people, and a clear separation of powers.